2017
DOI: 10.1002/cbic.201600701
|View full text |Cite
|
Sign up to set email alerts
|

Design and Discovery of New Combinations of Mutant DNA Polymerases and Modified DNA Substrates

Abstract: Chemical modifications can enhance the properties of DNA by imparting nuclease resistance and generating more-diverse physical structures. However, native DNA polymerases generally cannot synthesize significant lengths of DNA with modified nucleotide triphosphates. Previous efforts have identified a mutant of DNA polymerase I from Thermus aquaticus DNA (SFM19) as capable of synthesizing a range of short, 2'-modified DNAs; however, it is limited in the length of the products it can synthesize. Here, we rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…There are numerous examples of transferable mutations across XNA substrates and polymerases. A recent report [154] details engineering of a previously described Taq mutant to better incorporate 2′ modified XNAs. From kinetic data on incorporation of different 2′ modified nucleotides, relevant mutations from the literature were chosen based on the hypothesis that the rate-limiting step may be recognition of the modified primer strand.…”
Section: Rational Engineering Of Xna Polymerases: Translation Of Mutamentioning
confidence: 99%
“…There are numerous examples of transferable mutations across XNA substrates and polymerases. A recent report [154] details engineering of a previously described Taq mutant to better incorporate 2′ modified XNAs. From kinetic data on incorporation of different 2′ modified nucleotides, relevant mutations from the literature were chosen based on the hypothesis that the rate-limiting step may be recognition of the modified primer strand.…”
Section: Rational Engineering Of Xna Polymerases: Translation Of Mutamentioning
confidence: 99%
“…The concentrated enzyme stock should be returned to the -20 °C freezer immediately after use. NOTE: Because we primarily evaluate mutant DNA polymerases, we only use enzymes that have been expressed and purified in our laboratory using established methods 9,10 . For commercially purchased polymerases, users should be wary of optimal buffers for different proteins and their compatibility with the buffers described herein.…”
Section: Assay Runmentioning
confidence: 99%
“…To evaluate the ability of mutant DNA polymerases to synthesize M-DNA, we 9,10 , and others 11,12,13 typically use in vitro measurements of DNA polymerase activity, which are described in this manuscript. In these experiments, DNA polymerases are co-incubated with a labeled primer/template duplex and nucleoside triphosphate substrates; the products are evaluated by gel electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we assess whether commercial DNA polymerases have the latent ability to both reverse transcribe and amplify 2′-modified nucleotides in a single reaction. 2′-Fluoro-modified nucleic acids, which have been termed either 2′-fluoro-modified DNA 15,19 or 2′-fluoro-modified RNA (here, for the sake of clarity, we refer to this polymer as 2′-fluoromodified DNA as our synthesis enzyme is a DNA polymerase mutant and there are no 2′OH substitutions on any nucleotides of the oligonucleotide polymer), are among the most frequently used M-DNAs and have been used in miRNA 22 and in aptamers containing partially 2′F-substituted DNA or RNA. 23−26 In addition, 2′F M-DNA is widely commercially available as both the nucleoside triphosphate and a phosphoramidite, making it one of the most broadly accessible M-DNAs currently in use.…”
mentioning
confidence: 99%
“…23−26 While partially substituted 2′F M-DNA has been the focus of 2′F M-DNA applications due to the limited ability of RNA polymerase or DNA polymerases to synthesize fully substituted 2′F M-DNA, recent work has shown that mutant M-DNA polymerases can synthesize long (80-nucleotide) fully substituted 2′F M-DNA. 15 Importantly, this synthesis can be performed without manganese using substoichiometric enzyme levels with relatively short extension times (1 h). These conditions are significantly more mild than those typically used for other M-DNAs making 2′F M-DNA better suited to applications in synthetic biology that encode information ex vivo and, potentially, eventually in vivo.…”
mentioning
confidence: 99%